Soluble ST2 in the prediction of heart failure and death in patients with atrial fibrillation - Krittayaphong R. (2023)
Background: Biomarkers may be a useful marker for predicting heart failure (HF) or death in patients with atrial fibrillation (AF). Hypothesis: Soluble ST2 (sST2) may be a good biomarker for the prediction of HF or death in patients with AF. Methods: This is a prospective study of patients with nonvalvular AF. Clinical outcomes were HF or death. Clinical and laboratory data were compared between those with and without clinical outcomes. Univariate and multivariate analysis was performed to determine whether sST2 is an independent predictor for heart failure or death in patients with nonvalvular AF. Results: A total of 185 patients (mean age: 68.9 ± 11.0 years) were included, 116 (62.7%) were male. The average sST2 and N-terminal pro-brain natriuretic peptide (NT-proBNP) levels were 31.3 ± 19.7 ng/ml and 2399.5 ± 6853.0 pg/ml, respectively. Best receiver operating characteristic (ROC) cut off of sST2 for predicting HF or death was 30.14 ng/ml. Seventy-three (39.5%) patients had an sST2 level ≥30.14 ng/ml, and 112 (60.5%) had an sST2 level <30.14 ng/dl. The average follow-up was 33.1 ± 6.6 months. Twenty-nine (15.7%) patients died, and 33 (17.8%) developed HF during follow-up. Multivariate analysis revealed that high sST2 to be an independent risk factor for death or HF with a HR and 95% CI of 2.60 (1.41–4.78). The predictive value of sST2 is better than NT-proBNP, and it remained significant in AF patients irrespective of history of HF, and NT-proBNP levels. Conclusions: sST2 is an independent predictor of death or HF in patients with AF irrespective of history of HF or NT-proBNP levels.